Engaging innate immunity for targeting the epidermal growth factor receptor: Therapeutic options leveraging innate immunity versus adaptive immunity versus inhibition of signaling - Hintzen, Gabriele; Dulat, Holger J.; Rajkovic, Erich (Frontiers in Oncology, 2022)
The epidermal growth factor receptor (EGFR) is a key player in the normal tissue physiology and the pathology of cancer. Therapeutic approaches have now been developed to target oncogenic genetic aberrations of EGFR, found in a subset of tumors, and to take advantage of overexpression of EGFR in tumors. The development of small-molecule inhibitors and anti-EGFR antibodies targeting EGFR activation have resulted in effective but limited treatment options for patients with mutated or wild-type EGFR-expressing cancers, whilst therapeutic approaches that deploy effectors of the adaptive or innate immune system are still undergoing development. This review discusses EGFR-targeting therapies acting through distinct molecular mechanisms to destroy EGFR-expressing cancer cells. The focus is on the successes and limitations of therapies targeting the activation of EGFR versus those that exploit the cytotoxic T cells and innate immune cells to target EGFR-expressing cancer cells. The current landscape of clinically approved EGFR-targeting therapies and of those showing great promise in preclinical and clinical development, in particular the innate cell engagers, are discussed. Furthermore, this review highlights the potential to combine innate cell engagers with immunotherapies, to maximize their effectiveness, or with unspecific cell therapies, to convert them into tumor-specific agents.